The Protection of dependent self-employed workers against sexual harassment within the work place under labour laws in Kenya - Keilla, Kerubo Okari (Strathmore University, 2021)
The world of work as we know it today is constantly evolving majorly due to the ever-expanding service sector. The moribund traditional employment structures that had once informed the backdrop of labour legislation can no longer be sufficient for the Non-Standard forms of Employment recognized by the International labour Organisation. The protections of dependent self-employed workers against sexual harassment in Kenya is centered as the subject of this thesis. The study investigates whether they are adequately protected under employment laws in Kenya in comparison with other jurisdictions and proceeds to give recommendations on measures and mechanisms to ascertain the protection against sexual harassment within the work place
Submitted in partial fulfilment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School